2007
DOI: 10.1111/j.1462-5822.2007.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Echovirus infection causes rapid loss-of-function and cell death in human dendritic cells

Abstract: Summary Coxsackie B viruses (CVB) and Echoviruses (EV)form

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 64 publications
(77 reference statements)
1
67
0
Order By: Relevance
“…Bovine monocytes are CD32 positive and so were exposed to FMDV IC but were nonsusceptible to FMDV infection. Such differences in susceptibility between monocytes and DC have been reported for a range of viruses, including herpes simplex virus (HSV), echovirus, and poliovirus, where monocytes were found to be more resistant to infection than DC (33,40,60). In contrast, monocytes are more susceptible than moDC to CPE following influenza virus infection (8).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Bovine monocytes are CD32 positive and so were exposed to FMDV IC but were nonsusceptible to FMDV infection. Such differences in susceptibility between monocytes and DC have been reported for a range of viruses, including herpes simplex virus (HSV), echovirus, and poliovirus, where monocytes were found to be more resistant to infection than DC (33,40,60). In contrast, monocytes are more susceptible than moDC to CPE following influenza virus infection (8).…”
Section: Discussionmentioning
confidence: 82%
“…MoDC express the poliovirus receptor and are susceptible to infection (60). Similarly, human moDC could be infected by echovirus, but not by coxsackie B virus, and this again was related to appropriate receptor expression (33).…”
Section: Discussionmentioning
confidence: 96%
“…The innate response to CVB infections is poorly understood. Previous studies have shown that poliovirus infection inhibits proinflammatory cytokine secretion and the expression of antiviral cytokine receptors (10,37), while echovirus infection limits the ability of DCs to up-regulate costimulatory molecules or produce cytokines in response to Toll-like receptor stimulation (28). Because some members of the picornavirus family encode proteins with conserved functions, it is worth considering that one or more CVB3 proteins may be able to alter the expression of costimulatory molecules and/or the cytokine milieu, which could interfere with DC maturation or function.…”
Section: Discussionmentioning
confidence: 99%
“…Coxsackievirus B3 (CVB3) Nancy was kindly provided by R. Kandolf (University of Tübingen, Tübingen, Germany). Production of virus stocks and virus titrations were performed on buffalo green monkey cells as described previously (22). Serial 10-fold dilutions were tested in 96-well microtiter plates, and 50% tissue culture infective doses were calculated as described before (35).…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that infection of human monocyte-derived DCs with echovirus (EV), but not coxsackie B virus (CVB), results in rapid inhibition of TLR-mediated responses and massive cell death (22). As it is difficult to reconcile these in vitro effects with the generally mild clinical outcome of EV infections, we set out to investigate the conditions that could potentially alter DC susceptibility.…”
mentioning
confidence: 99%